Assessment of Major Causes of Calf Mortality in Urban and Periurban Dairy Production System of Ethiopia - Tsegaw Fentie; Sintayehu Guta; Gebreyes Mekonen; Wudu Temesgen; Achenef Melaku; Getachew Asefa; Shimelis Tesfaye; Ayalew Niguse; Bosenu Abera; Fikre Zeru Kflewahd; Birhanu Hailu; Feyissa Begna; et al. (Veterinary Medicine International)
A cross-sectional calf mortality study was conducted in urban and periurban dairy farms in Addis Ababa, special zones of Oromia and Amhara regions in July and August 2015. The objectives of the study were to estimate the annual mortality and to assess the major causes of calf mortality in the dairy farms. One-year retrospective data on calf mortality were collected from 330 farms by face-to-face interview using the pretested and structured questionnaire format and direct observation of farm practices. A logistic regression analysis was performed in order to identify the predictor variables associated with early calf mortality. Data were analysed using Statistical Package, Stata SE for Windows, version 12.0. The annual mean calf mortality from birth-to-weaning was reported as 18.5% (95% CI: 12.6, 24.3%). The prenatal loss due to fetal death and stillbirth was 10.1% (95% CI: 6.7, 13.6%). The overall annual loss due to fetal death and calf preweaning mortality was 26.7% (95% CI: 21.2, 32.2%). Age-specific mortality declined with increased age, and the highest mortality was recorded during the first month of life extending up to the third month of age. Disease was the most important causes of calf mortality (73.2%). Among the diseases, diarrhea (63%) and respiratory disorders (17%) were the important causes of calf mortality. Malpractices in calf management were identified, including restricted colostrum and milk feeding, poor care and supplemental feeding, and poor health management. Interventions in dairy cattle health and farm husbandry are recommended to control calf mortality.